Work-Life balance and psychological well-being in early adult single women of Javanese Ethnicity - Anugrah Imam Sarwono Putra; Arthur Huwae (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2024)
This study aims to investigate the impact of work-life balance on the psychological well-being of early adult single women who are Javanes-ethnic. A quantitative research method with regression analysis design was used in this study. The participants consisted of 435 early adult single women who work and are Javanese-ethnic, selected using incidental sampling technique. The measurement instruments used were the Work-Life Balance Scale (α=0.833) and the Ryff Psychological Well-Being Scale (α=0.858). The data analysis employed regression analysis using ANOVA. The research findings indicate that there is no significant influence of work-life balance on psychological well-being (t = 1.858 and sig. = 0.064). This suggests that there are other factors that influence the psychological well-being of early adult single women who work and are Javanese-ethnic. The implication of this study is the need for interventions that can enhance work-life balance for early adult single women to achieve a balance between their work and personal lives, leading to psychological well-being. Future research is expected to develop approaches to achieving psychological well-being for early adult single women who are Javanese-ethnic in managing their multiple roles both in their families and workplaces.